INCREASING PRODUCTIVITY OF YOUNG SIMMENTAL CATTLE ON THE BASIS OF INTENSIVE TECHNOLOGY IN UZBEKISTAN - Asrayev Usman Nasirovich (Galaxy International Interdisciplinary Research Journal, 2022)
The paper considers the impact of intensive cultivation of Simmental breed heifers on growth, development, reproductive ability and milk productivity by increasing the level of feeding by 20-30%. These researches showed that intensive breeding of experimental heifers allowed bringing the live weight at the age of 15.6 months to 391.4 kg and fruitful insemination, reducing the reception of litter for 50 days, increasing the milk productivity by 11.8% and at the age of 25-26 months transferring them to the main herd.